2015
DOI: 10.4050/jahs.60.011005
|View full text |Cite
|
Sign up to set email alerts
|

Study of Processing Conditions on the Forming of Ribbed Features Using Randomly Oriented Strands Thermoplastic Composites

Abstract: Compression molding of randomly oriented strands (ROS) composites offers the possibility to manufacture complex parts with a fast processing cycle. In this paper, effects of pressure, strand size, temperature, and material placement in the mold cavity on the quality of a T-shape part were studied experimentally with carbon/polyether ether ketone ROS composites. Minimum filling pressure was obtained for the consolidation of a 25-mm deep cavity. Parts processed at filling pressure showed a void content no greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
2
17
0
Order By: Relevance
“…Leblanc et al. 80 studied the effect of pressure, strand size, temperature and material placement in a 25.4 mm deep rib cavity and reported that low pressures were sufficient to fully consolidate parts with smaller strand (3.17 mm × 6.35 mm) of carbon/PEEK at 400°C. Parts processed at filling pressure (10 bars) had a void content <1.2% while high pressure (70 bars) decreased the void content to 0.44% and 0.03%.…”
Section: Part Level Studies On Ros Architecturementioning
confidence: 99%
“…Leblanc et al. 80 studied the effect of pressure, strand size, temperature and material placement in a 25.4 mm deep rib cavity and reported that low pressures were sufficient to fully consolidate parts with smaller strand (3.17 mm × 6.35 mm) of carbon/PEEK at 400°C. Parts processed at filling pressure (10 bars) had a void content <1.2% while high pressure (70 bars) decreased the void content to 0.44% and 0.03%.…”
Section: Part Level Studies On Ros Architecturementioning
confidence: 99%
“…Recent reports have described the state of the art for reuse and recycling of composite materials [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recycling of thermoset composites (particularly epoxies) presents a challenge due to their highly cross-linked structures and insolubility under mild conditions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Selezneva et al 15,16 determined mechanical properties of such composites as a function of both material and test specimen characteristics, identifying trends similar to those observed for thermoset composites, and proposed a stochastic approach for modeling mechanical performance. 17 Leblanc et al 18 studied the effect of processing conditions on the forming of ribbed features, showing that complex features can be produced if the molding pressure exceeds a sufficient filling pressure, and that initial strand placement can reduce mechanical performance if it creates merging flow fronts. Levy et al 19 proposed and demonstrated a model capable of predicting the inter-strand void content for discontinuous CF/ PEEK parts, and produced design charts relating process parameters, chip properties, and final part characteristics.…”
Section: Introductionmentioning
confidence: 99%